2012
DOI: 10.1002/adfm.201102373
|View full text |Cite
|
Sign up to set email alerts
|

A Single Component Conducting Polymer Hydrogel as a Scaffold for Tissue Engineering

Abstract: Conducting polymers (CPs) have exciting potential as scaffolds for tissue engineering, typically applied in regenerative medicine applications. In particular, the electrical properties of CPs has been shown to enhance nerve and muscle cell growth and regeneration. Hydrogels are particularly suitable candidates as scaffolds for tissue engineering because of their hydrated nature, their biocompatibility, and their tissue‐like mechanical properties. This study reports the development of the first single component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
204
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(208 citation statements)
references
References 48 publications
4
204
0
Order By: Relevance
“…[4,5] However, the electrically nonconductive nature of hydrogels impedes its use for excitable cells such as neural, skeletal and cardiac muscle, and bone cells. [6,7] To extend the utility of hydrogels, conducting 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 3 elements like metallic nanoparticles [8][9][10][11][12][13][14] and inherently conductive polymers (IHPs) [6,[15][16][17][18][19] have been incorporated within hydrogel matrices in order to add conductive properties to the 3D microenvironments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,5] However, the electrically nonconductive nature of hydrogels impedes its use for excitable cells such as neural, skeletal and cardiac muscle, and bone cells. [6,7] To extend the utility of hydrogels, conducting 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 3 elements like metallic nanoparticles [8][9][10][11][12][13][14] and inherently conductive polymers (IHPs) [6,[15][16][17][18][19] have been incorporated within hydrogel matrices in order to add conductive properties to the 3D microenvironments.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] The use of PANi in engineering cell-laden three-dimensional biomimetic constructs has been limited due to its difficult and non-biocompatible processing steps and its insolubility in common solvents. [17,[26][27][28] Previously, we have reported that PANi can be integrated with synthetic PEGDA and naturally derived gelatin methacrylate (GelMA) hydrogels in situ in order to develop 3D conductive-hydrogels that are sufficiently biocompatible with seeded cells. [29,30] However, like studies similar to ours, the harsh processing methods were incompatible with cell encapsulation approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, hydrogel materials, whose structures and functions are postmodulable multiple times, just like living tissues, have long been awaited [7][8][9][10] . Indeed, various applications are expected for hydrogels that are modulable noninvasively in desired time and space domains [11][12][13][14][15][16] .…”
mentioning
confidence: 99%
“…The conducting scaffold should also mimic the mechanical and topological environment of the targeted tissue or organ [8] . Construction of conducting scaffolds, which can satisfy all of the mentioned criteria, is an ongoing challenge.…”
Section: Introductionmentioning
confidence: 99%